2018
DOI: 10.1038/s41541-018-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

A combination of TLR-4 agonist and saponin adjuvants increases antibody diversity and protective efficacy of a recombinant West Nile Virus antigen

Abstract: Members of the Flaviviridae family are the leading causes of mosquito-borne viral disease worldwide. While dengue virus is the most prevalent, the recent Zika virus outbreak in the Americas triggered a WHO public health emergency, and yellow fever and West Nile viruses (WNV) continue to cause regional epidemics. Given the sporadic nature of flaviviral epidemics both temporally and geographically, there is an urgent need for vaccines that can rapidly provide effective immunity. Protection from flaviviral infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…We demonstrated that the antibody response in three participants with neuroinvasive WNV infection has the capacity to cause ADE of DENV2 in K562 cells and likely other DENV serotypes not tested given antibody cross-reactivity by ELISA was observed to all four DENV serotypes. The WNV envelope protein is a potential antigen of interest in the development of WNV vaccines, therefore, antibodies generated following WNV vaccination could potentially cause antibody-dependent enhancement of DENV virus [11, 12]. We recommend that assessments for the development of cross-reactive antibodies to other flaviviruses, including DENV, should be investigated as a safety measure during WNV vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the antibody response in three participants with neuroinvasive WNV infection has the capacity to cause ADE of DENV2 in K562 cells and likely other DENV serotypes not tested given antibody cross-reactivity by ELISA was observed to all four DENV serotypes. The WNV envelope protein is a potential antigen of interest in the development of WNV vaccines, therefore, antibodies generated following WNV vaccination could potentially cause antibody-dependent enhancement of DENV virus [11, 12]. We recommend that assessments for the development of cross-reactive antibodies to other flaviviruses, including DENV, should be investigated as a safety measure during WNV vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA vaccine encodes the protein prM and the E glycoproteins of the NY99 strain of WNV under the transcriptional control of the CMV/R promoter [ 70 ]. More than 95% of recipients who used this vaccine developed neutralizing antibodies, but this result was obtained only after administration of three doses 4 weeks apart (NCT00300417).…”
Section: West Nile Virus Diseasementioning
confidence: 99%
“…Therefore, mRNA vaccines may open a new window for an effective DENV vaccine. Based on this information, it is important to enhance vaccine efficacy by improving the design of safe, effective, and affordable vaccines against dengue, including the use of various adjuvants such as TLR agonist adjuvants ( Van Hoeven et al, 2018 ; Bidet et al, 2019 ).…”
Section: Challenges To Overcome In Denv Vaccine Developmentmentioning
confidence: 99%